Experimental Study on the Transport and Alteration Behavior of Aerosols From Low Density Powders for Acute Inhalation Toxicology Studies - Wessely, Benno; Stintz, Michael; Nolde, Juergen; Creutzenberg, Otto (Frontiers in Public Health, 2022)
Low density powders have a bulk density of less than 100 kg/m3 and are produced technically by flame pyrolysis of silicon tetrachloride (pyrogenic powders such as pyrogenic silica) or wet-chemically by sol-gel processes (e.g. silica-gel) or precipitation reactions using sodium silicate solution and a mineral acid. The transport and alteration behavior of aerosols from low density powders was investigated in a device for toxicological inhalation studies. The test conditions corresponded to those for acute toxicology studies according to OECD Guideline 436. The use of cascade impactors, required by guideline, has not proven successful for low density powders as the fragile agglomerate structures are destroyed during the measurement. As an alternative and non-invasive measurement method, laser diffraction spectroscopy has proved very successful in the present investigations. In particular, aerosols from pyrogenic powders of low density showed a distinctive tendency to re-agglomerate, especially at concentrations >500 mg/m3mm3. Investigation results indicate that aerosol particle size must be monitored over the entire acute inhalation test period for acute inhalation studies to be performed reliably.